Associations among social needs, health and healthcare utilization, and desire for navigation services among US Medicaid beneficiaries with type 2 diabetes. (11th March 2021) - McQueen, Amy; Kreuter, Matthew W.; Herrick, Cynthia J.; Li, Linda; Brown, Derek S.; Haire‐Joshu, Debra
Abstract: The purpose of this study was to better understand the number and types of social needs experienced by Medicaid beneficiaries with type 2 diabetes, and how their social needs are associated with key health indicators. Also examined were factors that influence patients' interest in navigation services for health and social needs to inform future interventions and service delivery. The study expands upon prior research, much of which has focused on only one social need (e.g., food insecurity) or one health outcome. The hypothesis was that among individuals with type 2 diabetes, those with a greater number of social needs would report more health‐related problems and be more interested in receiving social needs navigation services. Participants completed a cross‐sectional survey by phone ( n  = 95) or online ( n  = 14). Most (85%) reported having at least one social need ( M  = 2.5, SD  = 2.2), most commonly not having enough money for unexpected expenses (68%) or necessities like food, shelter and clothing (31%), medical costs (24%), and utilities (23%). Results supported our comprehensive conceptual model. Having more social needs was associated with greater perceived stress, diabetes distress, problems with sleep and executive and cognitive functioning, less frequent diabetes self‐care activities, more days of poor mental health and activity limitations, worse self‐reported health and more hospitalisations. Number of social needs also was positively associated with interest in having a social needs navigator. Social needs were not associated with days of poor physical health, BMI, self‐reported A1C or smoking status. Social needs were associated with a wide range of indicators of poor health and well‐being. Participants with the greatest social need burden were most open to intervention.